Interests in Petanque Sports Field Visitors Andi Makkasau Parepare City - Yuni Sahruni, Ade; Margaretha Warwuru, Priclya; Marlissa, Damaris (Indonesian Journal of Physical Education and Sport Science, 2023)
Study Purpose. In this study the aim was to find out the interest in petanque sport by visitors to the Andi Makkasau field in Parepare City, which in general, petanque sport is a sport that is still commonplace but is seen as a positive activity for the community in striving to achieve at the level of physical fitness while also increasing achievement. Materials and Methods. The population in this study were all visitors to the Andi Makkasau Field in the city of Parepare with a total of 30 people who regularly come to participate in petanque sports twice a week without specifying an age limit. The data collection technique instrument used a questionnaire by asking several questions in writing and then the respondents answered according to the instructions given. The data analysis technique that the researcher uses in this case is the quantitative descriptive analysis technique. Results. Research on the interest in petanque sports of Andi Makkasau field visitors in Parepare city in terms of intrinsic and extrinsic interest aspects, namely 6 people or (20%) have a low interest category, 10 people or (33.33%) low interest category, 8 people or (26 .67%) medium category, 4 people or (13.33%) high category and 2 people or (6.67%) have very high category. Conclusion. This figure is of course a concern in efforts to increase competence as a sport that has just joined in the city of Parepare which only has very high interest of 2 people.